Antibody response to the N and C-terminal regions of the Plasmodium vivax Merozoite Surface Protein 1 in individuals living in an area of exclusive transmission of P. vivax malaria in the north of Brazil - SOARES, I. S; OLIVEIRA, S. G; SOUZA, J. M; RODRIGUES, M. M (Acta tropica, 1999)
Recently, we found that a recombinant protein based on the 19 kDa C-terminal region of the Plasmodium vivax Merozoite Surface Protein 1 (PvMSP1(19)) was recognized by a large proportion of individuals naturally infected. The present study was designed to determine the prevalence of antibody to PvMSP1(19) in individuals from the village of Cotijuba, northern Brazil, where only P. vivax transmission occurs. Immuno-epidemiological studies on the prevalence of antibody to the C-terminus of PvMSP1 are of particular importance as this region of MSP1 is being intensively studied as a prime candidate for development of a vaccine against malaria. We evaluated the antibody response to PvMSP1(19), and compared it to the N-terminal region of PvMSP1 and to blood stage antigens. The total frequencies of individuals with IgG to blood stages, PvMSP1(19) or the N-terminal region of PvMSP1 were 76.6, 42.3 and 29.8%, respectively. The frequency of responders to PvMSP1(19) did not increase with age. However, the frequency of responders to this recombinant protein was significantly higher (77.4%) in individuals with a recent ( < 6 months) history of malaria, when compared to subjects whose last malaria attack occurred more than 6 months before (43.9%), or to individuals without a past history of symptomatic malaria (6.25%). These results confirm earlier studies by demonstrating that the PvMSP1(19) is highly immunogenic in individuals recently exposed to P. vivax malaria.